Monocyte subsets exhibit transcriptional plasticity and a shared response to interferon in SIV‐infected rhesus macaques. Issue 1 (14th December 2017) - Nowlin, Brian T.; Wang, John; Schafer, Jamie L.; Autissier, Patrick; Burdo, Tricia H.; Williams, Kenneth C.
Abstract: The progression to AIDS is influenced by changes in the biology of heterogeneous monocyte subsets. Classical (CD14++CD16–), intermediate (CD14++CD16+), and nonclassical (CD14+CD16++) monocytes may represent progressive stages of monocyte maturation or disparate myeloid lineages with different turnover rates and function. To investigate the relationship between monocyte subsets and the response to SIV infection, we performed microarray analysis of monocyte subsets in rhesus macaques at three time points: prior to SIV infection, 26 days postinfection, and necropsy with AIDS. Genes with a 2‐fold change between monocyte subsets (2023 genes) or infection time points (424 genes) were selected. We identify 172 genes differentially expressed among monocyte subsets in both uninfected and SIV‐infected animals. Classical monocytes express genes associated with inflammatory responses and cell proliferation. Nonclassical monocytes express genes associated with activation, immune effector functions, and cell cycle inhibition. The classical and intermediate subsets are most similar at all time points, and transcriptional similarity between intermediate and nonclassical monocytes increases with AIDS. Cytosolic sensors of nucleic acids, restriction factors, and IFN‐stimulated genes are induced in all three subsets with AIDS. We conclude that SIV infection alters the transcriptional relationship between monocyte subsets and that the innate immune response to SIV infection is conserved across monocyte subsets.